Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha

Wydawnictwo:Nowa Era

Rok wydania:2016

Rozwiąż równanie 4.6 gwiazdek na podstawie 10 opinii
  1. Liceum
  2. 2 Klasa
  3. Matematyka

`a)` 

`xne0\ \ \ =>\ \ \ D=RR\\{0}` 

 

`2/x=x+1\ \ \ |*x` 

`2=x^2+x\ \ \ |-2` 

`x^2+x-2=0` 

`Delta=1^2-4*1*(-2)=1+8=9` 

`sqrtDelta=3` 

`x_1=(-1-3)/2=-4/2=-2inD` 

`x_2=(-1+3)/2=2/2=1inD` 

Otrzymaliśmy dwa rozwiązania, oba należą do dziedziny. 

 

 

`b)` 

`xne0\ \ \ =>\ \ \ D=RR\\{0}` 

 

`-1/x=x+2\ \ \ |*x` 

`-1=x^2+2x\ \ \ |+1` 

`x^2+2x+1=0` 

`Delta=2^2-4*1*1=4-4=0` 

`x_0=(-2)/2=-1inD` 

 

 

 

`c)` 

`x+3ne0\ \ \ =>\ \ \ x ne-3\ \ \ =>\ \ \ D=RR\\{-3}` 

 

`4/(x+3)=x+3\ \ \ |*(x+3)` 

`4=(x+3)^2` 

`(x+3)^2-4=0\ \ \ \ \ \ |_(a^2-b^2=(a-b)*(a+b))`  

`(x+3-2)*(x+3+2)=0` 

`(x+1)*(x+5)=0` 

`x_1=-1inD` 

`x_2=-5inD` 

 

 

 

`d)` 

`6-xne0 \ \ =>\ \ \ xne6\ \ \ =>\ \ \ D=RR\\{6}` 

 

`9/(6-x)=x\ \ \ |*(6-x)` 

`9=6x-x^2\ \ \ |+x^2-6x` 

`x^2-6x+9=0\ \ \ \ \ |_(a^2-2ab+b^2=(a-b)^2)` 

`(x-3)^2=0` 

`x-3=0` 

`x=3inD` 

 

 

 

 

`e)` 

`xne0\ \ \ =>\ \ \ D=RR\\{0}` 

`6/x=x+5\ \ \ |*x` 

`6=x^2+5x\ \ \ |-6` 

`x^2+5x-6=0` 

`Delta=5^2-4*1*(-6)=25+24=49` 

`sqrtDelta=7` 

`x_1=(-5-7)/2=-12/2=-6inD`  

`x_2=(-5+7)/2=2/2=1inD`    

 

 

 

`f)`  

`xne0\ \ \ =>\ \ \ D=RR\\{0}` 

 

`-8/x=x+6\ \ \ |*x` 

`-8=x^2+6x\ \ \ |+8` 

`x^2+6x+8=0` 

`Delta=6^2-4*1*8=36-32=4` 

`sqrtDelta=2` 

`x_1=(-6-2)/2=-8/2=-4inD`  

`x_2=(-6+2)/2=-4/2=-2inD` 

 

 

`g)` 

`x+2ne0\ \ \ =>\ \ \ xne-2\ \ \ =>\ \ \ D=RR\\{-2}` 

 

`3/(x+2)=x\ \ \ |*(x+2)` 

`3=x^2+2x\ \ \ |-3` 

`x^2+2x-3=0` 

`Delta=2^2-4*1*(-3)=4+12=16` 

`sqrtDelta=4` 

`x_1=(-2-4)/2=-6/2=-3inD` 

`x_2=(-2+4)/2=2/2=1inD` 

 

 

 

`h)` 

`x-3ne0\ \ \ =>\ \ \ x ne3\ \ \ =>\ \ \ D=RR\\{3}` 

 

`-6/(x-3)=2x+1\ \ \ |*(x-3)` 

`-6=(2x+1)(x-3)` 

`-6=2x^2-6x+x-3 \ \ \ |+6` 

`2x^2-5x+3=0` 

`Delta=(-5)^2-4*2*3=25-24=1` 

`sqrtDelta=1` 

`x_1=(5-1)/(2*2)=4/4=1inD` 

`x_2=(5+1)/(2*2)=6/4=3/2inD`